Procedure-Related Access Site Pain Multimodal Management following Percutaneous Cardiac Intervention: A Randomized Control Trial. (24th January 2022) - Brogiene, Liuda; Urbonaite, Aiste; Baksyte, Giedre; Macas, Andrius
Abstract : Context . Approximately 1 in 20 patients undergoing the percutaneous cardiac intervention (PCI) experience severe procedure-related access-site (A-S) pain. The multimodal pain management model (MPM) can reduce the intensity and prevalence of pain and this approach was not investigated in the postprocedural pain management area. To address this, a randomized controlled trial was conducted in Hospital of Lithuanian University of Health Sciences Kauno klinikos in 2018. Methods . 137 patients who underwent PCI procedure via radial artery were randomly assigned (1 : 1) to the control (CG, n = 68) and intervention (IG, n = 65) groups. IG received MPM (paracetamol, ibuprofen, and the arm physiotherapy), CG received pain medication "as needed." Outcomes were assessed immediately after, 2, 12, 24, and 48 h, 1 week, and 1 and 3 months after PCI. The primary outcome was A-S pain prevalence and pain intensity numeric rating scale (NRS) 0–10. Results . Results showed that A-S pain prevalence during the 3-month follow-up period was decreasing. Statistically significant difference between the groups (CG versus IG) was after 24 h (41.2% versus 18.5, p = 0.005 ), 48 h (30.9% versus 1.5%, p ≤ 0.001 ), 1 week (25% versus 10.8%, p = 0.042 ), 1 month (23.5% versus 7.7%, p = 0.017 ) after the procedure. The mean of the highest pain intensity was after 2 h (IG-2.17 ± 2.07; CG-3.53 ± 2.69) and the lowest 3 months (IG-0.02 ± 0.12; CG-0.09 ± 0.45) after the procedure. A-S pain intensity mean scores were statistically significantly higher in CG during the follow-up period (Wilks' λ = 0.84 F (7, 125) = 3.37, p = 0.002 ). Conclusion . In conclusion, MPM approach can reduce A-S pain prevalence and pain intensity after PCI. More randomized control studies are needed.